Analysis of the Difference in RSET According to the Change in the Height of the Stairs in the School - Chang-Jun Choi; Ha-Sung Kong (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study, in order to evaluate the safety of evacuation by comparing and analyzing the RSET according to the height change of the stair, which is a vertical evacuation route in case of fire in a high school building, Evacuation simulation was run the Pathfinder program changed the height change of the stair to 0.16m, 0.18m, and 0.2m for each male students and female students. In the case of female students, it was analyzed that when the final RSET height was 0.18m, 1.2 seconds were shorter than when 0.16m, and were the same as at 0.2m. Male students also found that when the final RSET height was 0.18m, 2.3 seconds were shorter than when 0.16m, and 0.5 seconds shorter than when 0.2m. It was analyzed that even if the number of participants was increased and the evacuation simulation was executed, the safety of evacuation could be improved when the height change of the stair is 0.18m as the RSET when the height change of the stair is 0.2m is shorter than that of 0.16m and 0.18m.